Tribotechnical processes of the soil environment interaction with the working bodies of soil tillage and earthmoving machines reinforced with composite materials - Tykhyi, A.A.; Aulin, V.V.; Pashynskyi, M.V.; Borovik, A.Y. (Problems of Tribology, 2024)
The work presents the study results of the stress-strain state of the soil, as a continuous medium filled with abrasive particles under the action of the working bodies of soil tillage and earthmoving machines. One of the main properties of the soil, which determines the specifics of the force interaction of the working surfaces of the working bodies of soil tillage and earthmoving machines with the technological environment, is taken into account, namely the tendency of the contact layer of the treated layer to compaction. The relationship between stress in the soil and the wear of the working bodies of soil tillage and earthmoving machines has been established experimentally. A theoretical analysis is presented for the stress-strain state of the local region of the strengthened surface layer that is used in the working bodies of soil tillage and earthmoving machines, in which the filler, inclusion or strengthening phase is placed. An analysis of the contact characteristics of the stress-strain state and their changes during friction and wear was carried out based on the formulation and solution of the contact interaction problems of abrasive soil particles with the inhomogeneities of the composite coatings components based on ultra-high molecular weight polyethylene with fillers during strengthening of the working bodies of soil tillage and earthmoving machines. Computer modeling was performed to study the nature of stress distribution in the reinforced surface layer of the working bodies of soil tillage and earthmoving machines in the area of the contact zone in stationary and dynamic conditions. The contact problem is formulated, the boundary conditions and the solution in the form of components of the stress field are given. The characteristics of the filler, their content in the composite material and coating are taken into account, the relationship between the stress-strain state and wear is established.